Prevalence and molecular characterization of Salmonella isolated from wild birds in fresh produce environments - Smith, Jared C.; Varriano, Sofia; Roach, Kerrie; Snipes, Zach; Dawson, Joshua L.; Shealy, Justin; Dunn, Laurel L.; Snyder, William E.; Shariat, Nikki W. (Frontiers in Microbiology, 2023)
Wild birds pose a difficult food safety risk to manage because they can avoid traditional wildlife mitigation strategies, such as fences. Birds often use agricultural fields and structures as foraging and nesting areas, which can lead to defecation on crops and subsequent transfer of foodborne pathogens. To assess the food safety risk associated with these events, wild bird feces were collected from produce fields across the southeastern United States during the 2021 and 2022 growing seasons. In total 773 fecal samples were collected from 45 farms across Florida, Georgia, South Carolina, and Tennessee, and 2.1% (n = 16) of samples were Salmonella-positive. Importantly, 75% of Salmonella were isolated from moist feces, showing reduced Salmonella viability when feces dry out. 16S microbiome analysis showed that presence of culturable Salmonella in moist feces correlated to a higher proportion of the Enterobacteriaceae family. From the Salmonella-positive samples, 62.5% (10/16) contained multi-serovar Salmonella populations. Overall, 13 serovars were detected, including six most commonly attributed to human illness (Enteriditis, Newport, Typhimurium, Infantis, Saintpaul, and Muenchen). PCR screening identified an additional 59 Salmonella-positive fecal samples, which were distributed across moist (n = 44) and dried feces (n = 15). On-farm point counts and molecular identification from fecal samples identified 57 bird species, including for 10 Salmonella-positive fecal samples. Overall, there was a low prevalence of Salmonella in fecal samples, especially in dried feces, and we found no evidence of Salmonella transmission to proximal foliage or produce. Fecal samples collected in farms close together shared highly related isolates by whole genome sequencing and also had highly similar Salmonella populations with comparable relative frequencies of the same serovars, suggesting the birds acquired Salmonella from a common source.